Quest for Divinity: A Critical Examination of the Thought of Mahmud Muhammad Taha by Mohamed A. Mahmoud (Syracuse, New York: Syracuse University Press, 2007. 309 pages.) (American Journal of Islam and Society, 2008)
This important book critically examines the religious and political thoughtof Mahmud Muhammad Taha, a significant twentieth-century reformistthinker who is hardly known outside of Sudanese studies. Other works inEnglish on Taha include Abdullahi al-Na`im’s translated The SecondMessage of Islam (Syracuse University Press: 1987), written by a disciplewhose own reformist positions derive from Taha’s methodology andthought. This study provides an introduction to Taha’s thought for scholarsof twentieth-centuryMuslim reformers. It highlights the radical nature of hisSufi-grounded thought and the originality of his interpretations of theQur’an and the hadith based upon Muslim scholars as well as westernDarwinian and Marxist-Hegelian thought. The author stresses the importanceand originality of Taha’s thoughtwithin the broader context of the contemporaryMuslim world. His appearance on the scholarly “radar screen”has not yet fully been realized; indeed, al`Na`im has drawn more attentionin theWest than his mentor Taha ever did.As the founder of the nationalist al-Hizb al-Jamhuri in 1945, whichlater became the Republican Brotherhood (al-Jamhouriyeen), Taha wasboth a significant political figure and a controversial theologian who wasfamously tried and executed for the “crime” of apostasy in 1985. His executionis widely viewed as having sparked the democratic uprising (intifada)that overthrew Numeiri’s military dictatorship, which had engineered hisexecution ...